Organizational resilience factors of startups: An exploratory case study - Matos, F.; Monteiro, M.; Rosa, Á.; Campino, J. (Proceedings of the 18th European Conference on Management Leadership and Governance, ECMLG 2022, 2022)
In an increasingly competitive environment subject to uncontrollable risks, the continuity of organizations can be severely threatened, and the decision-making process takes place under circumstances of great uncertainty. Therefore, it is necessary to develop strategies and competencies that allow the business to thrive. Startups, particularly technology-based ones, are an essential source of innovation. However, several studies indicate that approximately 60% of Startups fail in the first five years of business. To succeed, startups need to develop skills that allow them to rapidly evaluate their decisions and options, and to identify what is vital for the survival of their business. Thus, organizational resilience becomes of paramount importance to those companies. The term resilience is used in different areas of knowledge, but all the definitions share common ground regarding the concept: it describes the ability of an element to return to its normal state after a period of stress and crisis. The main objective of this exploratory research developed in Portugal is to identify the resilience factors of technological Startups. It is also intended to contribute to the design and development of instruments which promote organizational resilience in technological ecosystems. The current research follows the case study methodology based on a sample of 10 technological startups collected from the Startup Leiria ecosystem (Portugal). The Startup Leiria is an incubator of startup ventures which makes it a prime source of data and knowledge. The main findings point out the necessity to develop agility skills in Startup ecosystems. It was concluded that resilient organizations are characterized by having the ability to anticipate, respond, adapt, and recover from a disruptive event. The uniqueness of this study concerns its contribution to stimulate data-driven discussions regarding the necessity to implement programs for the reskilling of Startups in the context of their ecosystems.